Adequate velocity model as a basis for effective seismic imaging when mapping hydrocarbon traps associated with salt domes - Tiapkina, O.; Tiapkin, Yu.; Okrepkyj, O.I. (Geofizicheskiy Zhurnal, 2015)
This paper is the second one in a series of tutorials on the usage of modern migration methods for seismic imaging in areas of intense salt tectonics. In the paper, it is shown the importance of building an adequate velocity model for effective seismic imaging and subsequent mapping of hydrocarbon traps associated with salt domes. To solve this problem, ray-based tomography, delayed imaging time scans and full waveform inversion are successfully used. Moreover, the paper shows the importance of evaluating properly and taking into account velocity anisotropy when making seismic images. This is demonstrated with real seismic data obtained in areas of heavy halokinesis.